2016
DOI: 10.1161/hypertensionaha.116.07493
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Regulates Renal Sodium Transporters and Renal Injury in Angiotensin II–Induced Hypertension

Abstract: Angiotensin II (Ang II)-induced hypertension is associated with an increase in T cell production of interleukin 17A (IL-17A). Recently, we reported that IL-17A−/− mice exhibit blunted hypertension, preserved natriuresis in response to a saline challenge, and decreased renal sodium hydrogen exchanger 3 (NHE3) expression after 2 weeks of Ang II infusion compared to wild type (WT) mice. In the current study, we performed renal transporter profiling in mice deficient in IL-17A or the related isoform, IL-17F, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 24 publications
(36 reference statements)
4
126
1
1
Order By: Relevance
“…160 Recent data indicate that IL17A modulates expression and function of the sodium hydrogen exchanger 3 and sodium chloride cotransporter in renal tubular epithelial cells, thus promoting sodium reuptake by these cells. 161 IL-17A also promotes aortic stiffening and directly stimulates production of collagen by aortic fibroblasts. 162 …”
Section: Reactive Oxygen Species Inflammation and Hypertensionmentioning
confidence: 99%
“…160 Recent data indicate that IL17A modulates expression and function of the sodium hydrogen exchanger 3 and sodium chloride cotransporter in renal tubular epithelial cells, thus promoting sodium reuptake by these cells. 161 IL-17A also promotes aortic stiffening and directly stimulates production of collagen by aortic fibroblasts. 162 …”
Section: Reactive Oxygen Species Inflammation and Hypertensionmentioning
confidence: 99%
“…Albuminuria is a well-known marker of glomerular injury and has been shown to increase following Ang II infusion in WT C57BL/6J mice (4,6). For these experiments, we used tg CD4cre mice as a secondary control.…”
Section: T Cell Sgk1 Deficiency Attenuates Ang Ii-induced Hypertensionmentioning
confidence: 99%
“…Evidence from our group and others has demonstrated that hypertension is an inflammatory disease characterized by T cell activation, infiltration of target organs such as the kidney and vasculature, and production of cytokines that lead to salt and water retention, vascular dysfunction, and renal injury (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the study also demonstrated that IL-17A stimulated NHE3 expression in cultured kidney cells mediated by serum and glucocorticoid regulated kinase 1 phosphorylation. 59 …”
Section: Role Of the Pt Nhe3 Regulation In Experimental Angii Hypertementioning
confidence: 99%